Algorithmic Democracy: Ethical Considerations on the Datafication of the Public Scope - Calvo, Patrici (Revista del CLAD Reforma y Democracia, 2019)
Currently the convergence of Artificial Intelligence, Big Data and the Internet of Things allows the algorithmization, datafication and hyperconnectivity of the entire scope of human activity, such as economics, welfare or politics. Together with the disaffection of civil society towards the current democratic models, this fact is generating new democratic proposals based on the supposed objectivity, morality, representability and neutrality of mathematical models based on artificial neural networks of machine learning. Using a hermeneutic-critical methodology in the study of bibliographical sources, the objective of the present work is to show the challenges, limits and consequences that underlie the diverse democratic proposals based on mathematical models of decision, massive data and the hyperconnectivity of the digital society.